Implementation of traditional massage “Peuseul” to improve the welfare of pregnant women in Sukamulya Village, Ciamis Regency - Ningrum, Widya Maya; Purnamasari, Kurniati Devi; Fatimah, Siti (Galuh International Journal of Community Service and Development, 2024)
Peuseul is a traditional massage practice that has long been used in Sundanese culture to support the well-being of pregnant women. In addition to helping to reduce physical discomfort, such as back pain and leg cramps, the practice also strengthens the spiritual and emotional connection between pregnant women and their communities. However, Peuseul is at risk of being lost if it is not preserved and adapted to modern health standards. Therefore, this community service program was designed to preserve, promote, and integrate Peuseul into the health care of pregnant women in Tatar Sunda, (Sundanese land). This program involved intensive training for local paraji, socialization of Peuseul benefits in the community, and the provision of free Peuseul services for pregnant women. The training was focused on massage techniques, the use of safe herbal herbs, as well as knowledge of the anatomy of pregnancy. Socialization is carried out through community meetings, printed media, and educational videos. The evaluation of the program was conducted through questionnaires and interviews with pregnant women as well as paraji (the massage person) to measure the physical and emotional impact of the practice. The results of the program showed the success of paraji training in providing safe and effective Peuseul services. The socialization increased public awareness about the importance of Peuseul in prenatal care. Pregnant women who received Peuseul reported improvements in physical and emotional well-being, including a reduction in back pain and anxiety facing childbirth. This program proved that Peuseul had a significant value in supporting the health of pregnant women, both physically and emotionally, and could be adapted according to modern health standards.